Gradient-thickness electrode for lithium ion battery and preparation method and application of gradient-thickness electrode
By using a multi-layer coating process in the lithium-ion battery electrode, the gradient distribution of active materials and conductive agents is controlled, and the problems of internal stress concentration and electrochemical performance in the charging and discharging process of traditional electrodes are solved, which significantly improves the battery Energy density and cycle stability are suitable for high-rate charging and discharging applications.
Patent Information
- Application Number
- CN202411492154.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional lithium-ion battery electrodes are prone to internal stress concentration and uneven electrochemical performance during charging and discharging, resulting in poor cycling stability and rate performance, and the lithium ion transmission of thick electrodes is hindered, affecting the energy density and service life of the battery.
By using a multi-layer coating process, the electrode material is rich in conductive agent near the current collector side and away from the current collector side to realize conductive agent and active substances. The gradient distribution of the lithium ion transmission path is optimized and the conductivity is enhanced.
It significantly improves the energy density, power density and cycling stability of the battery, reduces the risk of electrode shedding, extends the service life of the battery, and improves the mechanical stability and fast charging and discharging capabilities of the battery.
Smart Images

Figure CN119230753A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a gradient thick electrode for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] Driven by the rapid development of electric vehicles, mobile communication devices and energy storage systems, the market has increasingly stringent requirements for the energy density, cycle life and safety of lithium-ion batteries. The traditional lithium-ion battery electrode preparation method mainly adopts a single-coated thin electrode design, which limits the loading amount of active materials and leads to limited energy storage capacity of the battery. This design is gradually becoming inadequate in today's battery technology that pursues higher energy density. In addition, single-coated electrodes are prone to internal stress concentration and uneven electrochemical performance during the charge and discharge cycle, which not only weakens the battery's cycle stability and rate performance, but may also shorten the battery's service life and efficiency due to ion transmission resistance and severe polarization.
[0003] In order to overcome these limitations, thick electrode technology has become a research hotspot due to its potential in improving battery energy density. However, increasing the thickness of the electrode sheet will cause the following problems: (1) During the drying stage of electrode preparation, as the electrode thickness increases, the traditional single-coating electrode faces the risk of uneven drying and cracking; (2) The electrode sheet peeling force deteriorates, and the risk of electrode detachment is high; (3) Thicker electrodes require lithium ions to migrate longer distances during the charging and discharging process. At the same time, due to the poor wetting effect of the electrolyte on the thick electrode sheet, lithium ion transmission is hindered, forming electrochemical polarization; (4) Under fast charging conditions, the lithium ion transmission capacity of the thick electrode is limited, affecting the fast charging performance of the battery. These problems may damage the mechanical stability and electrochemical properties of the electrode, and thus affect the safety performance of the battery. At present, the existing technology mainly uses a multi-layer coating process to effectively alleviate the problems of electrode cracking and poor electrode sheet peeling force during the drying process. However, this method still cannot solve the problems of lithium ion transmission obstruction and electrochemical polarization, and the battery's rate performance and cycle stability are still poor.
[0004] Therefore, it is particularly important to develop new electrode structures and preparation processes to improve battery performance. Summary of the invention
[0005] In view of the above shortcomings of the prior art, one of the objects of the present invention is to provide a method for preparing a gradient thick electrode for a lithium-ion battery. A multi-layer coating process is adopted. By controlling the content of active materials and conductive agents in each layer of slurry, the electrode material is rich in conductive agents on the electrode side close to the current collector, and rich in active substances on the electrode side far from the current collector. The conductive agent and active substances are distributed in a gradient in the electrode material, thereby improving the electrochemical properties and mechanical stability of the electrode material.
[0006] The above object of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a gradient thick electrode for a lithium ion battery comprises the following steps:
[0008] S1. Prepare slurry A, slurry B and slurry C respectively, wherein slurry A, slurry B and slurry C all include active materials, conductive agents and binders, and the active material content of slurry A, slurry B and slurry C is slurry A < slurry B < slurry C from low to high, and the conductive agent content is slurry C < slurry B < slurry A from low to high;
[0009] S2. Slurry A is coated on the current collector, and slurry B is coated after drying and solidification, and slurry C is coated after drying and solidification. The gradient thick electrode is obtained after drying and sheeting.
[0010] The present invention adopts a multi-layer coating process, and by controlling the content of active materials and conductive agents in each layer of slurry, the electrode material near the current collector side is rich in conductive agents, and the electrode far from the current collector side is rich in active substances, and the conductive agent and active substances are distributed in a gradient in the electrode material, so that the transmission path of lithium ions inside the electrode can be optimized, and at the same time, the purpose of enhancing conductivity and reducing polarization is achieved, the uniformity of current distribution inside the battery is improved, and the energy density, power density and cycle stability of the battery are significantly improved, and the electrochemical performance of the electrode material is improved. In addition, the method of the present invention can also improve the bonding force between the electrode coating and the current collector, reduce the risk of electrode shedding, improve the mechanical stability of the electrode material, and extend the battery cycle life.
[0011] The method of the present invention coats the next layer of slurry after the previous layer of slurry is solidified, which can ensure good bonding between the layers and the overall performance of the electrode. The method of the present invention has the advantages of simple preparation process, easy operation, and high production efficiency, and is suitable for large-scale industrial production to meet the needs of high-performance batteries.
[0012] Preferably, the weight ratio of the active substance, the conductive agent and the binder in the slurry A is (70~80): (10~25): (5~10); the weight ratio of the active substance, the conductive agent and the binder in the slurry B is (80~90): (5~10): (5~10); the weight ratio of the active substance, the conductive agent and the binder in the slurry C is (90~95): (2.5~5): (2.5~5).
[0013] Preferably, in step S2, the coating conditions are as follows: the coating thicknesses of the slurries A, B and C are the same, and the coating speeds of the slurries B and C are lower than the coating speed of the slurry A.
[0014] Preferably, the coating thickness is 5-5000 μm, the coating speed is 0.5-10 m / min, and the coating temperature is 20-150° C.
[0015] Preferably, the drying in step S2 can be performed by air drying or laser drying, which can avoid cracking of the electrode material during the drying process and ensure the integrity and stability of the electrode layer.
[0016] Preferably, the active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel cobalt lithium manganese oxide ternary material, natural graphite, artificial graphite, silicon oxygen material, and silicon carbon material.
[0017] Preferably, the conductive agent includes at least one of carbon black, graphene and carbon nanotubes.
[0018] Preferably, the binder includes at least one of sodium carboxymethyl cellulose, polyvinylidene fluoride, and polyimide.
[0019] Another object of the present invention is to provide a gradient thick electrode for a lithium ion battery prepared by the preparation method.
[0020] Another object of the present invention is to provide a lithium-ion battery with the gradient thick electrode.
[0021] Compared with the prior art, the present invention is beneficial in that:
[0022] (1) The present invention controls the content of active materials and conductive agents in each layer of slurry, so that the electrode near the current collector in the electrode material is rich in conductive agents, and the electrode far from the current collector is rich in active substances, and the conductive agents and active substances are distributed in a gradient in the electrode material, thereby optimizing the distribution of active substances inside the electrode, reducing polarization, and improving ion transmission efficiency, thereby significantly improving the energy density and power density of the battery. In addition, the method of the present invention enables the active substances and conductive agents to be distributed inside the electrode according to a specific gradient, which can achieve uniform distribution of current inside the battery and significantly improve the overall performance of the battery. This design is particularly suitable for application scenarios that require high-rate charging and discharging, such as electric vehicles and mobile communication equipment, and meets the needs of these fields for fast charging and discharging capabilities of batteries.
[0023] (2) The present invention distributes the active material and the conductive agent in the electrode material according to a specific gradient, thereby achieving a uniform distribution of stress inside the electrode and improving the cycle stability of the battery.
[0024] (3) The method of the present invention can effectively enhance the bonding force between the electrode coating and the current collector, reduce the risk of electrode detachment, extend the cycle life of the battery, and improve the structural stability and service life of the battery.
[0025] (4) The method of the present invention can effectively avoid cracking of the electrode during drying and use, thereby improving the reliability and durability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The cross-sectional SEM images of the electrodes obtained in Example 1 and Comparative Examples 1 to 3;
[0027] Figure 2 The planar SEM images of the electrodes obtained in Comparative Examples 2 and 3;
[0028] Figure 3 The figure is a rate performance diagram of the electrodes obtained in Example 1 and Comparative Examples 1-2;
[0029] Figure 4 The graphs are the cycle performances of the electrodes obtained in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the present invention, the active material can be at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel cobalt lithium manganese oxide ternary material, natural graphite, artificial graphite, silicon oxide material, silicon carbon material, the conductive agent can be at least one of carbon black, graphene, carbon nanotubes, and the binder can be at least one of sodium carboxymethyl cellulose, polyvinylidene fluoride, and polyimide, which has little effect on the performance of the electrode material. For illustration only, the active material of the following embodiments and comparative examples is LiFePO4, the conductive agent is conductive carbon black, and the binder is polyvinylidene fluoride.
[0032] Example 1
[0033] This embodiment provides a method for preparing a gradient thick electrode for a lithium ion battery, comprising the following steps:
[0034] S1. Prepare slurry A, slurry B and slurry C respectively;
[0035] Preparation of slurry A: dissolving the active material, the conductive agent and the binder in an N-methylpyrrolidone solvent in a mass ratio of 75:15:10, wherein the mass of the solvent is the same as that of the solid powder, and stirring and mixing them thoroughly to obtain slurry A;
[0036] Preparation of slurry B: dissolving the active material, the conductive agent and the binder in an N-methylpyrrolidone solvent in a mass ratio of 80:10:10, wherein the mass of the solvent is the same as that of the solid powder, and stirring and mixing them thoroughly to obtain slurry B;
[0037] Preparation of slurry C: dissolving the active material, the conductive agent and the binder in an N-methylpyrrolidone solvent at a mass ratio of 90:5:5, wherein the mass of the solvent is the same as that of the solid powder, and stirring and mixing them thoroughly to obtain slurry C;
[0038] S2. Slurry A was evenly coated on aluminum foil with a thickness of 16 μm. The coating thickness was controlled at 200 μm, the coating speed was 100 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 , then placing the coated electrode in a drying oven and drying at 60° C. for 30 minutes to evaporate the solvent and solidify the slurry to form a first electrode layer;
[0039] S3. Slurry B was evenly coated on the first electrode layer. The coating thickness was controlled at 200 μm, the coating speed was 50 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 , then placing the coated electrode in a drying oven and drying at 60° C. for 30 minutes to evaporate the solvent and solidify the slurry to form a second electrode layer;
[0040] S4. Slurry C was evenly coated on the second electrode layer. The coating thickness was controlled at 200 μm, the coating speed was 50 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 The coated electrode was then placed in a drying oven and dried at 60 °C for 30 min to evaporate the solvent and solidify the slurry to obtain a gradient thickness electrode.
[0041] Example 2
[0042] The preparation method of the gradient thick electrode for lithium ion battery in this embodiment is basically the same as that in Example 1, except that, in step S1, the mass ratio of the active material, the conductive agent and the binder in slurry A is 70:25:5; the mass ratio of the active material, the conductive agent and the binder in slurry B is 85:10:5; the mass ratio of the active material, the conductive agent and the binder in slurry C is 90:5:5.
[0043] Example 3
[0044] The preparation method of the gradient thick electrode for lithium ion battery in this embodiment is basically the same as that in Example 1, except that, in step S1, the mass ratio of the active material, the conductive agent and the binder in slurry A is 80:10:10; the mass ratio of the active material, the conductive agent and the binder in slurry B is 90:5:5; the mass ratio of the active material, the conductive agent and the binder in slurry C is 95:2.5:2.5.
[0045] Comparative Example 1
[0046] This comparative example provides a method for preparing a gradient thick electrode for a lithium ion battery, comprising the following steps:
[0047] S1. Prepare slurry A, slurry B and slurry C respectively: the operation is the same as in Example 1;
[0048] S2. Slurry C was evenly coated on aluminum foil with a thickness of 16 μm. The coating thickness was controlled at 200 μm, the coating speed was 100 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 , then placing the coated electrode in a drying oven and drying at 60° C. for 30 minutes to evaporate the solvent and solidify the slurry to form a first electrode layer;
[0049] S3. Slurry B was evenly coated on the first electrode layer. The coating thickness was controlled at 200 μm, the coating speed was 50 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 , then placing the coated electrode in a drying oven and drying at 60° C. for 30 minutes to evaporate the solvent and solidify the slurry to form a second electrode layer;
[0050] S4. Slurry A was evenly coated on the second electrode layer. The coating thickness was controlled at 200 μm, the coating speed was 50 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 The coated electrode was then placed in a drying oven and dried at 60 °C for 30 min to evaporate the solvent and solidify the slurry to obtain a gradient thickness electrode.
[0051] That is, compared with Example 1, the coating order of the slurries in this comparative example is adjusted to slurry C, slurry B, and slurry A.
[0052] Comparative Example 2
[0053] This comparative example provides a method for preparing a gradient thick electrode for a lithium ion battery, comprising the following steps:
[0054] S1. Preparation of slurry D: The active material, the conductive agent and the binder are dissolved in N-methylpyrrolidone solvent in a mass ratio of 81.67:10:8.33. The mass of the solvent is the same as the mass of the solid powder. Slurry D is obtained after sufficient stirring and mixing.
[0055] S2. Slurry D was evenly coated on aluminum foil with a thickness of 16 μm. The coating thickness was controlled at 200 μm, the coating speed was 100 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 , then placing the coated electrode in a drying oven and drying at 60° C. for 30 minutes to evaporate the solvent and solidify the slurry to form a first electrode layer;
[0056] S3. Slurry D was evenly coated on the first electrode layer. The coating thickness was controlled at 200 μm, the coating speed was 50 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 , then placing the coated electrode in a drying oven and drying at 60° C. for 30 minutes to evaporate the solvent and solidify the slurry to form a second electrode layer;
[0057] S4. Slurry D was evenly coated on the second electrode layer. The coating thickness was controlled at 200 μm, the coating speed was 50 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 The coated electrode was then placed in a drying oven and dried at 60 °C for 30 min to evaporate the solvent and solidify the slurry to obtain a gradient thickness electrode.
[0058] That is, compared with Example 1, the first, second, and third electrode layers of this comparative example all use the same ratio of slurry D, ensuring the uniform distribution of active materials and conductive agents inside the electrode. This design is intended to keep the total amount of active materials and conductive agents of the two gradient thick electrodes of this comparative example and Example 1 consistent, so as to compare the effects of two different electrode structures on battery performance.
[0059] Comparative Example 3
[0060] S1. Preparation of slurry D: The operation was the same as in Comparative Example 2;
[0061] S2. Slurry D was evenly coated on aluminum foil with a thickness of 16 μm. The coating thickness was controlled at 600 μm, the coating speed was 100 cm / min, the working temperature was maintained at 30 °C, and the coating area was set to 15 × 20 cm 2 , and then the coated electrode was placed in a drying oven and dried at 60 °C for 30 min to evaporate the solvent and solidify the slurry to obtain a thick electrode.
[0062] That is, compared with Comparative Example 2, this comparative example adopts a single coating process.
[0063] Figure 1 The cross-sectional SEM images of the thick electrodes obtained in Example 1 and Comparative Examples 1 to 3 are shown in FIG. Figure 1 (a) is the gradient thick electrode of Example 1, Figure 1 (b) is the gradient thick electrode of Comparative Example 1; Figure 1 (c) is the electrode of Comparative Example 2; Figure 1 (d) is the electrode of comparative example 3; by comparison Figure 1 (a) and Figure 1 (d) It can be seen that compared with the homogeneous electrode obtained by single coating, the cross-section of the gradient thick electrode of Example 1 of the present invention shows a continuous microstructure without obvious stratification. The uniformity of this structure helps to improve the transmission efficiency of lithium ions inside the electrode, thereby optimizing the charge and discharge performance of the battery.
[0064] Figure 2 The planar SEM images of the thick electrodes obtained in Comparative Examples 2 and 3 are shown in FIG. Figure 2 (a) is the thick electrode of Comparative Example 2, Figure 2 (b) is the thick electrode of comparative example 3. It can be seen that the electrode surface obtained by the multi-layer coating process presents a complete and continuous morphology, while the electrode surface obtained by the single coating process has cracks. This shows that the multi-layer coating process can effectively improve the mechanical stability of the electrode, reduce cracks that may occur during drying and subsequent battery use, and thus enhance the overall performance of the electrode.
[0065] Application Examples
[0066] The electrodes obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were compacted, cut and cleaned, and placed in a vacuum drying oven to further remove the residual solvent to ensure the dryness and cleanliness of the electrodes; finally, the prepared electrodes were used as positive electrodes, a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing 1M LiPF6 was used as an electrolyte (the volume ratio of EC to DMC in the mixed electrolyte was 1:1), graphite was used as a negative electrode, Celgard 2325 was used as a separator, and CR2032 stainless steel was used as a battery shell to assemble a button cell for electrochemical performance testing.
[0067] The results of electrochemical performance tests show that the strategy adopted in Examples 1 to 3, i.e., the electrode close to the current collector is rich in conductive agent, while the electrode far from the current collector is rich in active material, further enables the conductive agent and active material to be gradiently distributed in the electrode material. This design can effectively optimize the distribution of active materials inside the electrode, thereby reducing polarization, improving ion transfer efficiency, and significantly improving the rate performance and cycle performance of the battery.
[0068] Figure 3 The rate performance of the half-cells assembled from the electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 is compared. It can be seen from the figure that the battery of Example 1 can reach 160.87 mAh·g at a current density of 0.1C. -1 The reversible capacity is still 119.75 mAh g at a high current density of 2C. -1 The reversible capacity of the battery is 2.37W, and when it returns to a low current, there is no significant loss in capacity. In addition, the battery of Example 1 has the highest discharge capacity retention rate at different rates, showing excellent rate performance. This result verifies the rationality of the gradient structure design of the present invention, which effectively reduces the polarization during high-rate charge and discharge by optimizing the transmission path of lithium ions inside the electrode, thereby improving the charge and discharge efficiency of the battery.
[0069] Figure 4 The cycle performance comparison diagram of the electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 at 1C current density shows that after the same number of cycles, the battery capacity decay rate of Example 1 is the lowest, showing the best cycle stability. This shows that the gradient thick electrode design of the present invention not only improves the rate performance of the battery, but also significantly improves the cycle life of the battery. This design effectively delays the aging process of the electrode material by reducing the volume expansion and stress concentration of the electrode during the charge and discharge process, thereby extending the service life of the battery.
[0070] In summary, the present invention not only improves the rate performance of the battery, but also enhances the cycle stability of the battery by precisely controlling the gradient distribution of the active material and the conductive agent inside the electrode, thereby achieving a significant improvement in the battery performance.
[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a gradient thick electrode for a lithium ion battery, characterized in that: The following steps are involved: S1. Prepare slurry A, slurry B and slurry C respectively, wherein slurry A, slurry B and slurry C all include active materials, conductive agents and binders, and the active material content of slurry A, slurry B and slurry C is slurry A < slurry B < slurry C from low to high, and the conductive agent content is slurry C < slurry B < slurry A from low to high; S2. Slurry A is coated on the current collector, and slurry B is coated after drying and solidification, and slurry C is coated after drying and solidification. The gradient thick electrode is obtained after drying and sheeting.
2. The method for preparing a gradient thick electrode for a lithium ion battery according to claim 1, characterized in that: The weight ratio of the active material, the conductive agent and the binder in the slurry A is (70~80): (10~25): (5~10); the weight ratio of the active material, the conductive agent and the binder in the slurry B is (80~90): (5~10): (5~10); the weight ratio of the active material, the conductive agent and the binder in the slurry C is (90~95): (2.5~5): (2.5~5).
3. The method for preparing a gradient thick electrode for a lithium ion battery according to claim 1, characterized in that: In step S2 , the coating conditions are as follows: the coating thicknesses of the slurries A, B and C are the same, and the coating speeds of the slurries B and C are lower than the coating speed of the slurry A.
4. The method for preparing a gradient thick electrode for a lithium ion battery according to claim 1, characterized in that: The coating thickness is 5~5000μm, the coating speed is 0.5~10m / min, and the coating temperature is 20~150℃.
5. The method for preparing a gradient thick electrode for a lithium ion battery according to claim 1, characterized in that: The active material includes at least one of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, nickel cobalt lithium manganese oxide ternary material, natural graphite, artificial graphite, silicon oxygen material, and silicon carbon material.
6. The method for preparing a gradient thick electrode for a lithium ion battery according to claim 1, characterized in that: The conductive agent includes at least one of carbon black, graphene, and carbon nanotubes.
7. The method for preparing a gradient thick electrode for a lithium ion battery according to claim 1, characterized in that: The binder includes at least one of sodium carboxymethyl cellulose, polyvinylidene fluoride and polyimide.
8. A gradient thick electrode for a lithium ion battery prepared by the method according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: Comprising the gradient thick electrode as described in claim 8.
Citation Information
Patent Citations
Preparation method of multi-layer coating pole piece
CN111370649A
High-load electrode, preparation method and lithium ion battery thereof
CN111430664A
Preparation method of multi-layer composite electrode and lithium ion battery of multi-layer composite electrode
CN115020642A
Composite positive pole piece, preparation method therefor, and lithium ion battery containing same
WO2020134707A1
Cited By
Thick electrode and preparation method thereof
CN122659047A
